Pengaruh Diabetes Self-Management Education and Support (DSME/S) Terhadap Kualitas Hidup pada Pasien Diabetes Melitus Tipe 2 - Anis Fitri Nurul Anggraeni; Rondhianto Rondhianto; Peni Perdani Juliningrum (Pustaka Kesehatan, 2018)
Type 2 DM is a chronic disease requiring long-term care, so it needs self-management education toprevent the complication. The patient's inability to perform self-care can reduce the quality of life. DSME/Sis one of education which facilitates knowledge, skills, patient abilities, and family support in self-care.DSME/S is given in the form of discharge planning to improve knowledge and skills in self-care. Thisresearch aimed to analyze the effect of Diabetes Self-Management Education and Support (DSME/S) onquality of life of patients with type 2 diabetes mellitus in RSD dr. Soebandi. The research design wasquasi experimental with pre-test post-test with control group design. A number of samples were 30 peopledivided into two groups: 15 people in the treatment group and 15 people in the control group. DSME/Swas conducted in 6 sessions. Sessions 1-4 were performed in the hospital and sessions 5-6 wereperformed at the patient’s home. The data were analyzed by using dependent t test and independent ttest which significance level of 0.05. The result of t-dependent test indicated that there was significantdifferent quality of life between pre-test and post-test in the treatment group (p = 0.001) and control group(p = 0.002). The result of Independent t test showed a significant difference between treatment group andcontrol group (p = 0.001). The enhancement of quality of life on the treatment group was greater than thecontrol group. The conclusion showed that there was significant effect of DSME/S on the quality of life oftype 2 DM patients. DSME/S could improve patient self-care knowledge and abilities in controlling bloodsugar and prevent complications may effect of quality of life. Nurses can apply DSME/S in healthpromotion programs to type 2 DM patients in hospital. Keywords: Type 2 diabetes mellitus, quality of life, DSME/S